Answer:
(x + 3/2)² + (y - 2)² = 25/4
Explanation:
(x - h)² + (y - k)² = r²
(0,0)
(0 - h)² + (0 - k)² = r²
h² + k² = r²
(-3,0)
(-3 - h)² + (0 - k)² = r²
9 + 6h + h² + k² = r²
9 + 6h + r² = r²
9 + 6h = 0
h = -9/6 = -3/2
(1,2)
(1 - h)² + (2 - k)² = r²
1 - 2h + h² + 4 - 4k + k² = r²
5 - 2h - 4k + h² + k² = h² + k²
5 - 2(-3/2) - 4k = 0
8 = 4k
k = 2
(x - (-3/2))² + (y - 3)² = r²
(x + 3/2)² + (y - 2)² = r²
Use any point to find r²
(0 + 3/2)² + (0 - 2)² = r²
9/4 + 4 = r²
r² = 25/4
(x + 3/2)² + (y - 2)² = 25/4